DEVELOPMENT OF INTEGRATED ELECTROCHEMISTRY TEACHING MATERIAL BASED CONTEXTUAL FOR VOCATIONAL HIGH SCHOOL IN MACHINE ENGINEERING DEPARTEMENT - Wiwik Widodo (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2017)
The chemistry teaching at Vocational High School which tends to be theoretical and not directly connected to vocational lesson has caused students to have low interest, low motivation, and low achievement. The problem is becoming more complex due to limited time allotment and limited teaching materials. One of the efforts to solve the problem is by providing the relevant teaching material using contextual learning approach. The aims of this Research and Development (RD) research are: (1) to produce an appropriate chemistry teaching material on electrochemistry integrated with skill program subjects using Contextual approach for Vocational High School students of Machinery Engineering Department; (2) to know the feasibility of development result of teaching material. The development of the teaching material uses 4D developmental model from Thiagarajan et al consisting of four phases namely Define, Design, Develop, and Desiminate. The dominate phase was not done. The scores of evaluation of the feasibility or the appropriateness of the product from the content expert are 88.75% (very feasible) for the teachers’ book and 91.25% (very feasible) for the students’ book. The expert on media gave 89.25% (very feasible) for the teachers’ book and 89.9% (very feasible) for the students’ book. The result of readability test shows that the teachers’ book is feasible (83.81%) and the students’ book is very feasible (93.61%).Keywords: Teaching material on electrochemistry, Machinery Engineering Department of Vocational High School, Contextual Approach